FLEXURAL STRENGTH AND DUCTILITY OF ULTRA HIGH-PERFORMANCE CEMENT-BASED COMPOSITES (UHP-CC) - AbdulRidha, Aseel AbdulAzeez; Danha, Lubna Salim; Hamid, Marawan Mohammed; Abdul-Husain, Zinah Asaad Abdul-Husain (Journal of Applied Engineering Science, 2022)
It has been known that concrete is weak in tension, so it requires some additional materials to have ductile behavior and enhance its tensile response. Thus, steel fibers came into use due to their advantage in controlling cracks and enhance the tensile behavior of concrete. In this study, the behavior and improvement in flexural tensile strength and strain capacity of ultra-high-performance cement-based composites (UHP-CC) were investigated. Two main variables were examined, namely the content of silica fume and steel fibers with percentages of (0%, 10%, 20% and 30%) and (0%, 1%, 2% and 3%) respectively. The experimental results show that, in the non-fibrous UHP-CC matrix, after the first crack initiation, the inclusion of steel fibers upgrades the behavior of the matrix from brittle to a plastic one and the specimen with a 1% steel fibers ratio failed immediately after crack initiation showing no possible occurrence of strain hardening or multiple cracking. In UHP-CC specimens with steel fibers of more than 1% the tensile failure was more ductile and accompanied by the development of the main crack and many multiple secondary cracks. it was found that the load increased even after the cracks initiation (strain hardening behavior) and thereafter showed gradual declination. It is revealed that after the peak point, one of the cracks widens and becomes critical, which defines the onset of crack localization showing no more development of cracks. Under increased deformation, the critical crack will open describing the stage of fibers pull-out. It was observed that the increase of the ratio of steel fibers in the range of (0% - 3%) caused a significant increase in flexural tensile strength by 244%, whereas the increase in compressive strength was only 12%.
Keywords: flexural tensile strength, ultra-high performance, steel fiber, strain hardening, ductility